My profession, however, is being Joan Fuster - Antoni Furió (Catalan Historical Review)
This article sets out to examine the figure, work and literary and political significance of Joan Fuster on the centennial of his birth and 30 years after his death. Joan Fuster, the most important essayist in Catalan in the twentieth century, cut from the same cloth as Eugeni d’Ors and Josep Pla, is a polyhedric personality with many faces: man of letters, civil intellectual, poet, scholar, literary critic, historian of literature and culture, translator, editor, newspaper columnist, thinker, civic referent, cultural and political activist, father of the Catalan Lands… This article makes a brief survey of his literary and public career as a writer, from the biographical and historical circumstances of his entrée into Catalan literature and culture to the continued relevance of his literary output and political proposals.